Advantages of the split-leg supine position single-port plus one laparoscopic surgery approach - Wang Xin; Yu Yongkui; Qin Zimin; Xu Lei; Wang Haojie; Xie Jinyi; Wu Yiju; Xu Zihou; Chen Peinan; Liu Qi; Li Haomiao; Wang Zongfei; et al. (Scientific Reports)
Abstract The goal of this study was to compare the advantages of conventional laparoscopic surgery (CLS) and the split-leg supine position single-port plus one laparoscopic surgery (SSP SILS + 1) in esophageal surgery. This study enrolled 73 patients who previously underwent radical esophagectomy for esophageal cancer from August 2021 to February 2023. Among them, 36 patients underwent SSP SILS + 1, whereas the remaining 37 patients underwentCLS. Surgical time, bleeding volume, number of dissected lymph nodes, incision length, and postoperative abdominal pain score between the two groups of patients were compared using either the Student’s t-test or chi-square test. Time of abdominal incision (1.4 ± 0.2 min vs. 5.2 ± 0.7 min, p < 0.001) was shorter in patients in the SSP SILS + 1 group compared with those in the CLS group. However, the average incision length was shorter in the SSP SILS + 1 group compared with that in the CLS group (35.4 ± 4.0 cm vs. 4.6 ± 4.1 cm, p < 0.001). Notably, the pain score on postoperative day (POD) 1 was lower in the SSP SILS + 1 group compared with that in the CLS group (5.7 ± 0.7 vs.6.3 ± 0.7, p = 0.001). The SCAR score was also lower in the SSP SILS + 1 group compared with that in the CLS group (3.5 ± 0.9 vs. 8.3 ± 1.4, p = 0.019). There was no significant difference in the number of dissected abdominal lymph nodes and positive lymph nodes (p > 0.01) between the two groups. The SSP SILS + 1 intervention offers multiple benefits over conventional surgical procedures, encompassing shorter incision length and pain scores on POD 1. In accelerated rehabilitation surgery for esophageal cancer, this surgical procedure demonstrated high safety, feasibility.